1980
DOI: 10.1021/ar50148a001
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of tetrahymanol by Tetrahymena pyriformis: mechanistic and evolutionary implications

Abstract: Polyprenoids constitute a diverse, widely distributed group of natural products derived biologically from (3fi)-mevalonic acid1,2 (1). Based on geochemical3 and other studies,4 it was inferred that the biosynthetic processes of polyprenoids evolved in the very early stages of evolutionary development.5,6 Although polyprenoids play a vital role in numerous life processes, e.g., as sex or corticosteroidal hormones, as bile acids, in vision, in defense mechanisms, etc., it appears that their primary biological fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…The study of the biosynthesis of this pentacyclic triterpene showed that it was formed from mevalonic acid , and thus from squalene, but without the intermediate epoxysqualene Caspi, 1980). The cyclization of squalene is not oxidative and the oxygen atom comes from water, not from the atmosphereresearch having shown that the biosynthesis of tetrahymanol takes place in either aerobic or anaerobic conditions Zander and Caspi, 1969;Zander, Greig, and Caspi, 1970).…”
Section: Ho H H H Tetrahymanolmentioning
confidence: 99%
“…The study of the biosynthesis of this pentacyclic triterpene showed that it was formed from mevalonic acid , and thus from squalene, but without the intermediate epoxysqualene Caspi, 1980). The cyclization of squalene is not oxidative and the oxygen atom comes from water, not from the atmosphereresearch having shown that the biosynthesis of tetrahymanol takes place in either aerobic or anaerobic conditions Zander and Caspi, 1969;Zander, Greig, and Caspi, 1970).…”
Section: Ho H H H Tetrahymanolmentioning
confidence: 99%
“…In an early investigation on the biosynthesis of tetrahymanol (14), in the protozoan T. pyriformis, the Caspi group demonstrated that during the cyclization process of the squalene precursor in D 2 O label from the solvent is incorporated exclusively in the 3bposition of the product, and that the OH group in the other terminal ring of 14 is derived from a H 2 O molecule (rather than from dioxygen) and thus represent the outcome of an (anti-Markovnikov) addition to the last double bond of the cyclizing chain [104]. The beautiful simplicity of this case, with its evident requirement for an all-chair folding of the aliphatic substrate, is a good testimonial for the general validity of the major postulates of the 1955 proposal.…”
Section: See [9f] [9e]mentioning
confidence: 99%
“…Squalene:hopene cyclase (SHC) from the thermoacidophilic bacterium Alicyclobacillus acidocaldarius has been well studied, and it was established that the enzyme binds squalene (1) in all-chair conformation, initiating the sequential carbon-carbon bonds forming reaction by an acid-catalyzed protonation of a terminal double bond. 9 No methyl or hydride migration takes place during the sequential ring-forming reactions. [4][5][6][7][8] On the other hand, the formation of tetrahymanol (6) by squalene:tetrahymanol cyclase (STC) from the protozoan Tetrahymena pyriformis is initiated by a proton attack on a terminal double bond of squalene, folded in all-chair conformation, but followed by addition of H 2 O to the resulting gammaceranyl C-21 cation (5) (Scheme 1(b)).…”
Section: Introductionmentioning
confidence: 99%
“…The polycyclization first produces the hopanyl C-22 carbocation (2) with a five-membered E-ring, which is followed by either regiospecific proton elimination from the terminal Z-methyl (Me-30) group or addition of H 2 O at the cationic center yielding hop-22(29)-ene (3) (80%) or hopan-22-ol (4) (20%) (Scheme 1(a)). 4,6,7,[10][11][12][13] Thus, the formation of lanosterol (9), which is the biosynthetic precursor of cholesterol, is initiated by an oxirane ring opening of (3S)-2,3-oxidosqualene (7) folded in chair-boat-chair conformation. 9 No methyl or hydride migration takes place during the sequential ring-forming reactions.…”
Section: Introductionmentioning
confidence: 99%